Healing power of papaya : a holistic health book on how to avoid acidosis, allergies, and other health disorders - Simonsohn, Barbara (Kathmandu : Pilgrims Publishing, 2000)
In her lively and descriptive health handbook, best-selling German author Barbara Simonsohn shares knowledge that native peoples from all over the world have successfully practiced for centuries. The "power fruit" papaya is virtually a universal remedy with a large spectrum of anti-inflammatory effects against many health disorders and diseases.
Includes bibliographical references and index.
Keywords: z